Foraminiferal Mn/Ca as Bottom‐Water Hypoxia Proxy: An Assessment of Nonionella stella in the Santa Barbara Basin, USA. Issue 11 (28th October 2021) - Brinkmann, I.; Ni, S.; Schweizer, M.; Oldham, V. E.; Quintana Krupinski, N. B.; Medjoubi, K.; Somogyi, A.; Whitehouse, M. J.; Hansel, C. M.; Barras, C.; Bernhard, J. M.; Filipsson, H. L.
Abstract: Hypoxia is of increasing concern in marine areas, calling for a better understanding of mechanisms leading to decreasing dissolved oxygen concentrations ([O2 ]). Much can be learned about the processes and implications of deoxygenation for marine ecosystems using proxy records from low‐oxygen sites, provided proxies, such as the manganese (Mn) to calcium (Ca) ratio in benthic foraminiferal calcite, are available and well calibrated. Here we report a modern geochemical data set from three hypoxic sites within the Santa Barbara Basin (SBB), USA, where we study the response of Mn/Caforam in the benthic foraminifer Nonionella stella to variations in sedimentary redox conditions (Mn, Fe) and bottom‐water dissolved [O2 ]. We combine molecular species identification by small subunit rDNA sequencing with morphological characterization and assign the SBB N. stella used here to a new phylotype (T6). Synchrotron‐based scanning X‐ray fluorescence (XRF) imaging and Secondary Ion Mass Spectrometry (SIMS) show low Mn incorporation (partition coefficient D Mn  < 0.05) and limited proxy sensitivity of N. stella, at least within the range of dissolved [O2 ] (2.7–9.6 μmol/l) and Mnpore‐water gradients (2.12–21.59 μmol/l). Notably, even though intra‐ and interspecimen Mn/Ca variability (33% and 58%, respectively) was only partially controlled by the environment, Mn/Caforam significantly correlated with both pore‐water Mn and bottom‐water [O2 ]. However, the prevalent suboxic bottom‐water conditions and limited dissolved [O2 ] range complicate the interpretation of trace‐elemental trends. Additional work involving other oxygenation proxies and samples from a wider oxygen gradient should be pursued to further develop foraminiferal Mn/Ca as an indicator for hypoxic conditions. Key Points: Benthic foraminiferal Mn/Ca is explored as low‐oxygen proxy using synchrotron‐based X‐ray fluorescence (XRF) nano‐imaging and ion‐beam trace‐element analysis The new phylotype Nonionella sp . T6 is linked to Nonionella stella in a combined molecular‐morphological species identification approach Foraminiferal Mn/Ca correlates positively with bottom‐water dissolved oxygen within the narrow gradient of suboxia ([O2 ] < 10 μmol/l)